1967
DOI: 10.1111/j.1748-1716.1967.tb03603.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart Volume during Prolonged Exercise in the Supine and Sitting Position

Abstract: The roentgenological heart volume was studied in 10 healthy young men during prolonged continuous exercise of constant intensity in the sitting position and in 6 subjects also in the supinr position. The work load was on an average 760.0 kpm/min in the sitting and 758.3 kpm/min in the supine position. The heart rate in the sitting position after 3–9 min exercise was 139.5 beats/min and 171.0 beats/min at the end of work, mean work time 56.5 min. The corresponding figures in the supine position were 127.8 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…A similar sharp rise in Ppa m at flows above 350 % of normal was reported a few years later in isolated perfused lungs (120). However, subsequent studies repeatedly reported a linear increase in Ppa m as a function of flow in isolated perfused lungs (59,236) as well as in intact human beings studied using the unilateral balloon occlusion technique (to double the flow in the contralateral lung) and/or exercise (18,44). There has been a recent report of a “take-off” pattern of Ppa m -Q relationships in normal subjects at exercise (216) reminiscent of the pioneering work of Cournand.…”
Section: Pulmonary Hemodynamics At Exercise In Healthy Humansmentioning
confidence: 99%
“…A similar sharp rise in Ppa m at flows above 350 % of normal was reported a few years later in isolated perfused lungs (120). However, subsequent studies repeatedly reported a linear increase in Ppa m as a function of flow in isolated perfused lungs (59,236) as well as in intact human beings studied using the unilateral balloon occlusion technique (to double the flow in the contralateral lung) and/or exercise (18,44). There has been a recent report of a “take-off” pattern of Ppa m -Q relationships in normal subjects at exercise (216) reminiscent of the pioneering work of Cournand.…”
Section: Pulmonary Hemodynamics At Exercise In Healthy Humansmentioning
confidence: 99%
“…3 (40)(41)(42)(43)(44)(45)(46)(47)(48). In addition, it has been demonstrated that a reduction of heart size, measured from chest roentgenograms, occurs in normal subjects in the sitting posture as compared with the supine (49)(50)(51). Recently, Rapaport, Wong, Escobar, and Martinez (52) have shown a diminution of right ventriclular end-diastolic volume when patients without congestive heart failure were tilted to the 60°upright position.…”
Section: During Isoproterenol Infusionmentioning
confidence: 99%
“…It is well established that cardiac output increases in proportion to work demands and then remains constant, both in healthy sedentary males and in coronary patients (Wade and Bishop, 1962;Ekelund and Holmgren, 1964;Ekelund et al, 1967;Hartley et al, 1969). However, the time course of cardiac output adaptation was found to be faster in healthy subjects (Jones and Reeves, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Though cardiac output values during continuous submaximal work are similar in healthy men and in coronary patients, the total output of oxygenated blood during an exercise period is greater in normal men. Ekelund et al (1967) reported an increase of 30 beats per minute (bpm) between the 10th and the 60th minute of work. Grimby et al (1966) found an increase of 10 to 12 bpm and Ekblom (1970) 20 bpm during an hour of pedalling.…”
Section: Discussionmentioning
confidence: 99%